Consumption in Indonesia: an application of ARDL panel data - Eddy Gunawan, Azka Rizkina, Aliasuddin, (Opción, 2019)
This study aims to analyze the influence of income, inflation, and population towards consumption in Indonesia by using panel ARDL panel. Panel data in this study is from 2008 to 2017 and covers 34 provinces, with a total of 340 samples. The results showed that income, inflation, and population affect the consumption of both the short and long run. Short-term influence is better rather than long-term. In conclusion, the income has an influence on long and short-run investments, this is because future income expected received higher in the future, compare to current consumption, more income, the larger consumption.